How well do you see what you hear? The acuity of visual-to-auditory sensory substitution - Haigh, Alastair; Brown, David J.; Meijer, Peter; Proulx, Michael J. (Frontiers in Psychology, 2013)
Sensory substitution devices (SSDs) aim to compensate for the loss of a sensory modality, typically vision, by converting information from the lost modality into stimuli in a remaining modality. “The vOICe” is a visual-to-auditory SSD which encodes images taken by a camera worn by the user into “soundscapes” such that an experienced user can extract information about their surroundings. Here we investigated how much detail was resolvable during the early induction stages by testing the acuity of blindfolded sighted, naïve vOICe users. Initial performance was well above chance. Participants who took the test twice as a form of minimal training showed a marked improvement on the second test. Acuity was slightly but not significantly impaired when participants wore a camera and judged letter orientations “live”. A positive correlation was found between participants’ musical training and their acuity. The relationship between auditory expertise via musical training and the lack of a relationship with visual imagery, suggests that early use of a sensory substitution device draws primarily on the mechanisms of the sensory modality being used rather than the one being substituted. If vision is lost, audition represents the sensory channel of highest bandwidth of those remaining. The level of acuity found here, and the fact it was achieved with very little experience in sensory substitution by naïve users is promising.